2016
DOI: 10.1016/j.hal.2015.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating cyanobacterial harmful algal blooms in aquatic ecosystems impacted by climate change and anthropogenic nutrients

Abstract: Mitigating the global expansion of cyanobacterial harmful blooms (CyanoHABs) is a major challenge facing researchers and resource managers. A variety of traditional (e.g., nutrient load reduction) and experimental (e.g., artificial mixing and flushing, omnivorous fish removal) approaches have been used to reduce bloom occurrences. Managers now face the additional effects of climate change on watershed hydrologic and nutrient loading dynamics, lake and estuary temperature, mixing regime, internal nutrient dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
289
0
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 517 publications
(305 citation statements)
references
References 108 publications
(88 reference statements)
8
289
0
8
Order By: Relevance
“…A proliferation of Cyanobacteria has been recorded in lacustrine phytoplanktonic communities, and studies have highlighted the possible role of climate change in promoting toxic blooms, although considerably different responses to temperature increase have been recorded among various Cyanobacteria species and among genetic strains [8,9,12,[55][56][57][58][59][60]. Moreover, these changes in lake ecosystems can lead to the introduction of allochthonous populations of Cyanobacteria, with different and not-always-identified toxicological features [4,55].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A proliferation of Cyanobacteria has been recorded in lacustrine phytoplanktonic communities, and studies have highlighted the possible role of climate change in promoting toxic blooms, although considerably different responses to temperature increase have been recorded among various Cyanobacteria species and among genetic strains [8,9,12,[55][56][57][58][59][60]. Moreover, these changes in lake ecosystems can lead to the introduction of allochthonous populations of Cyanobacteria, with different and not-always-identified toxicological features [4,55].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, these organisms are also capable of adapting to anthropogenic modifications of aquatic environments [5], such as enhanced nutrient loading or increasing temperatures. The literature has reported that climate change is likely to stimulate the development of harmful Cyanobacteria (e.g., [6][7][8][9][10][11][12][13][14]). Regional and global warming, with an associated increase in temperature and variability in rainfall patterns, causes changes in nutrients, sediment delivery, sediment-water exchange and metabolism, water residence time, and vertical stratification [6,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anthropic interferences through the input of nutrients in aquatic environments (in addition to climatic changes) can increase cyanobacterial harmful algal blooms (cyanoHABs) (Paerl and Huisman, 2009;Paerl and Otten, 2013;Paerl et al, 2016). The conditions that cause these blooms have become increasingly more frequent in inland waters worldwide, especially during dry seasons (Carmichael and Boyer, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…As our understanding of the toxins associated with cyanobacteria increase and our ability to detect the various toxins in biologic samples expand, linking exposure to illness will become easier. In addition, given the association between increasing temperatures and increased frequency of cyanobacteria blooms around the world, the incidence of cyanobacteria-associated illness will likely increase (17). Changing climates and anthropogenic activities are also likely to have an impact; therefore, healthcare providers and veterinarians will have to be vigilant when it comes to evaluating all aspects of adverse outcomes to cyanotoxins from recreational waters.…”
Section: Introductionmentioning
confidence: 99%